Caffeine intake in pregnancy: Relationship between internal intake and effect on birth weight. (December 2015) - Partosch, F.; Mielke, H.; Stahlmann, R.; Gundert-Remy, U.
Abstract: We used a physiologically based kinetic model to simulate caffeine blood concentration-time profiles in non-pregnant and pregnant women. The model predicted concentration-time profile was in good accordance with experimental values. With 200 mg, the safe dose per occasion in non-pregnant women, AUC and peak concentration in pregnant women were nearly twice that of non-pregnant women. In order to derive a safe dose for the pregnant women we estimated the dose in the pregnant women model taken at once which would not exceed AUC and peak concentration in the non-pregnant women of 200 mg as single dose. The resulting dose is 100 mg caffeine per occasion which we recommend as safe. The caffeine dose of 200 mg per day is declared as safe for pregnant women with respect to the foetus by EFSA based on results on reduced birth weight in epidemiological studies. We modelled AUC and peak concentration for different caffeine doses to investigate the relationship between internal caffeine exposure and risk measures of reduced birth weight from epidemiological studies. The graphical analysis revealed that the reduction in birth weight was related to AUC and peak concentration up to a dose of 250 mg caffeine. Highlights: A caffeine dose of 200 mg per day is safe for pregnant women. The model predicted concentration-time profile was in good accordance with experimental values. In pregnant women AUC and peak concentrations were nearly twice that of non-pregnant women. Internal exposure was related to the reduced birth weight.